Occupational exposure and risk of chronic obstructive pulmonary disease: a systematic review and meta-analysis. (2nd August 2016) - Alif, Sheikh M.; Dharmage, Shyamali C.; Bowatte, Gayan; Karahalios, Amalia; Benke, Geza; Dennekamp, Martine; Mehta, Amar J.; Miedinger, David; Künzli, Nino; Probst-Hensch, Nicole; Matheson, Melanie C.
ABSTRACT: Introduction : Due to contradictory literature we have performed a systematic review and meta-analyse of population-based studies that have used Job Exposure Matrices to assess occupational exposure and risk of Chronic Obstructive Pulmonary Disease (COPD). Areas covered : Two researchers independently searched databases for published articles using predefined inclusion criteria. Study quality was assessed, and results pooled for COPD and chronic bronchitis for exposure to biological dust, mineral dust, and gases/fumes using a fixed and random effect model. Five studies met predetermined inclusion criteria. The meta-analysis showed low exposure to mineral dust, and high exposure to gases/fumes were associated with an increased risk of COPD. We also found significantly increased the risk of chronic bronchitis for low and high exposure to biological dust and mineral dust. Expert commentary : The relationship between occupational exposure assessed by the JEM and the risk of COPD and chronic bronchitis shows significant association with occupational exposure. However, the heterogeneity of the meta-analyses suggests more wide population-based studies with older age groups and longitudinal phenotype assessment of COPD to clarify the role of occupational exposure to COPD risk.